Wage Inequality and Firm Growth - Mueller, Holger M.; Ouimet, Paige P.; Simintzi, Elena (American Economic Review, 2017)
We discuss firm-level evidence based on UK data showing that within-firm pay inequality–wage differentials between top- and bottom-level jobs–increases with firm size. Moreover, within-firm pay inequality rises as firms grow larger over time. Lastly, using wage data from 15 developed countries, we document a positive association between aggregate wage inequality at the country level and growth by the largest firms in the country. We conclude that part of what may be perceived as a global trend toward more wage inequality may be driven by an increase in the size of the largest firms in the economy.